2021
DOI: 10.1007/s00170-021-07340-8
|View full text |Cite
|
Sign up to set email alerts
|

Defining acoustic emission-based condition monitoring indicators for monitoring piston rod seal and bearing wear in hydraulic cylinders

Abstract: Fluid leakage from hydraulic cylinders is a major concern for the offshore industries as it directly affects hydraulic cylinder energy efficiency and causes environmental contamination. There have been attempts made in literature to develop robust condition monitoring techniques for hydraulic cylinders. However, most of these studies were performed to identify degradation of single components. Therefore, in this study, the aim is to monitor degradation of multiple components simultaneously in hydraulic cylinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…From the frequency domain analysis, the frequency band between 60 and 80 kHz was identified as the frequency band in which the seal wear is most prominent for the experiments conducted in this study. Thus, the identified frequency bands for seal wear of both the experiments of Shanbhag et al [23] and the current experiments in this paper occur in an overlapping frequency region. In Figure 13, the bandpass filtered RMS series from all tests show that the initial decreasing trend is removed from the RMS series.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…From the frequency domain analysis, the frequency band between 60 and 80 kHz was identified as the frequency band in which the seal wear is most prominent for the experiments conducted in this study. Thus, the identified frequency bands for seal wear of both the experiments of Shanbhag et al [23] and the current experiments in this paper occur in an overlapping frequency region. In Figure 13, the bandpass filtered RMS series from all tests show that the initial decreasing trend is removed from the RMS series.…”
Section: Discussionsupporting
confidence: 53%
“…In Figure 13, the bandpass filtered RMS series from all tests show that the initial decreasing trend is removed from the RMS series. This implies that the run-in period could not be identified in the experiments of Shanbhag et al [23] due to the bandpass filter. However, because the frequency band in the experiments of Shanbhag et al [23] increased to 100 kHz, whereas in the current research it was only shown up to 80 kHz, it cannot be excluded that the run-in period may be identified if the same bandpass filter were applied.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations